AN EVALUATION OF THE PRINCIPLE OF ADEQUACY IN THE U.S. AND INDONESIA RECIPROCAL TRADE AGREEMENT - Abdul Azis Ali Ramdlani; Rahmayanti (Journal of International Islamic Law, Human Right and Public Policy, 2026)
International trade today is no longer limited to the pricing of physical commodities; it has shifted toward the exchange of data, digital services, and high-tech investments. In this dynamic, the Adequacy Principle emerges as a key instrument. Article 56 of Law Number 27 of 2022 on Personal Data Protection (PDP) stipulates that cross-border data transfers are only permitted if the destination country has: (1) an equivalent or higher level of PDP, or (2) adequate and legally binding PDP measures, or (3) the consent of the data subject. To date, the Government Regulation—which is intended to establish the aforementioned equivalence criteria as a derivative of Article 56 has not yet been issued. In Article 3.2 Agreement Between The United States Of America And The Republic Of Indonesia On Reciprocal regarding Trade Data Transfers The principle of adequacy in U.S.-Indonesia trade relations remains asymmetrical. The United States tends to use adequacy as a leverage tool for global standardization, while Indonesia is still in a transitional phase of aligning domestic regulations (such as the PDP Law) to gain international recognition. Major Obstacles to Achieving a Mutually Beneficial Adequacy Status in U.S. and Indonesia Trade Relations include Differences in Cross-Border Data Protection Paradigms, Differences in Cross Border Data Protection Paradigms, Misalignment of Intellectual Property Rights (IPR) Enforcement Standards, and Regulatory Inconsistencies and Legal Uncertainty in Indonesia